2008
DOI: 10.1002/hep.22390
|View full text |Cite
|
Sign up to set email alerts
|

Loss of tolerance in C57BL/6 mice to the autoantigen E2 subunit of pyruvate dehydrogenase by a xenobiotic with ensuing biliary ductular disease

Abstract: There have been important advances in defining effector mechanisms for several human autoimmune diseases. However, for most human autoimmune diseases, the induction stage is less well defined and there are very few clues on etiology. Our laboratory has focused on defining the molecular basis of autoantibody recognition and epitope modification in primary biliary cirrhosis (PBC). Our work has demonstrated that antibodies to mitochondria (AMA), the hallmark of disease, are directed against a very conserved site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
153
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 166 publications
(175 citation statements)
references
References 37 publications
9
153
1
4
Order By: Relevance
“…One such halogenated compounds has been shown to induce AMA production in rabbits without requiring the peptide backbone of PDC-E2 [129] but failed to produce liver lesions (possibly in agreement with observations in humans where AMA is present several years prior to the appearance of liver injury) and disappeared when the stimulus was discontinued [130]. A different approach reported the induction of PBC-like liver lesions following longer follow-ups in guinea pigs [125] while a further study reported two new xenobiotic-induced PBC murine models based on the immunization with 2-octynoic acid of NOD.1101 [126] or C57BL/6 [127] mice. These two most recent models share the breakdown of tolerance in the absence of PDC-E2 molecules but fail to manifest the progression to liver cirrhosis.…”
Section: Chemical Compoundssupporting
confidence: 70%
See 1 more Smart Citation
“…One such halogenated compounds has been shown to induce AMA production in rabbits without requiring the peptide backbone of PDC-E2 [129] but failed to produce liver lesions (possibly in agreement with observations in humans where AMA is present several years prior to the appearance of liver injury) and disappeared when the stimulus was discontinued [130]. A different approach reported the induction of PBC-like liver lesions following longer follow-ups in guinea pigs [125] while a further study reported two new xenobiotic-induced PBC murine models based on the immunization with 2-octynoic acid of NOD.1101 [126] or C57BL/6 [127] mice. These two most recent models share the breakdown of tolerance in the absence of PDC-E2 molecules but fail to manifest the progression to liver cirrhosis.…”
Section: Chemical Compoundssupporting
confidence: 70%
“…The PDC-E2 structure exposes lipoic acid at the exterior of the protein complex making it accessible to chemical modification [123]. The role of xenobiotics in PBC is supported by serum reactivity against specific organic compounds with structures similar to lipoic acid [124]; further, two of these compounds (6-bromohexanoate and 2-octynoic acid) are capable of inducing AMA and PBC-like liver lesions in guinea pigs [125] and NOD.1101 [126] or C57BL/6 [127] mice, respectively. The ability of N. aromaticivorans to metabolize chemical compounds might link xenobiotics and bacteria in the etiology of PBC, as discussed in the previous paragraph.…”
Section: Chemical Compoundsmentioning
confidence: 99%
“…Mice immunized with 2 -octynoic acid serve as a unique PBC animal model showing autoimmune cholangitis, typical anti-mitochondrial autoantibodies, and elevated numbers of liver lymphoid cells with an increase in the number of CD8 ( + ) cells in the liver (Fig. 3 A, B) (42). However, difficulties are associated with demonstrating the localization of 2 -octynoic acid in the liver because of its small molecular size.…”
Section: Mechanisms Underlying Bile Duct Injury In Pbcmentioning
confidence: 99%
“…B6 Idd10 Idd18r2) mice immunised with 2-octynoic acid Unauthenticated Download Date | 5/9/18 8:02 AM (2-OA), coupled to BSA, had high AMA titers, portal inflammation, and cholangitis similar to human PBC (14).…”
Section: Xenobiotic Induced Pbcmentioning
confidence: 99%